Sosialisasi Peduli Lingkungan: Upaya Menanamkan Pentingnya Menjaga Kebersihan di SD No. 2 Ungasan - Rita Rahayu, Ni Putu Ayu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
A clean school environment is an important element that supports student comfort and health during the learning process. At SD No. 2 Ungasan, several conditions still exist that indicate the need to strengthen students' understanding of how to maintain environmental cleanliness, especially in terms of sorting waste and disposing of waste properly. In response to this, the Nusantara V KKN Team, Group 25 of I Gusti Bagus Sugriwa State Hindu University, Denpasar, conducted a socialization activity